Discrepancy between clinical and ultrasound remissions in rheumatoid arthritis: a multicentre ultrasound cohort study in Japan. (2nd November 2021) - Endo, Y; Kawashiri, S-Y; Nishino, A; Okamoto, M; Tsuji, S; Shimizu, T; Sumiyoshi, R; Igawa, T; Koga, T; Iwamoto, N; Ichinose, K; Tamai, M; et al.
Abstract : Objectives : Using multicentre ultrasound (US) cohort data among patients with rheumatoid arthritis (RA), we aimed to identify baseline factors that permit differentiation between two patient cohorts achieving US remission and clinical remission, and to determine the factors contributing to the discrepancy. Method : We reviewed 248 Japanese patients diagnosed with RA who underwent treatment with biological disease-modifying anti-rheumatic drugs at 13 centres. We performed US assessments of the synovia of 22 joints. We assessed the percentages of patients with clinical remission and US remission, defined as total power Doppler scores of 0 at 12 months. Results : The 87 patients who achieved US remission were divided into a group that achieved both clinical and US remission (n = 53) and a group that achieved US remission only (n = 34). Baseline factors that were significantly and independently associated with clinical remission at 12 months among patients who also achieved US remission included short disease duration, the presence of concomitant methotrexate use, and low patient global assessment score (p < 0.05, p < 0.05, and p < 0.005, respectively). Conclusions : RA patients with baseline high patient global assessment scores and long disease duration at baseline were unlikely to achieve clinical remission even after achieving US remission. Objective joint assessments using US provide additional information of potential importance for the management of RA.